Pembelajaran Online Anak Usia Dini Menggunakan Grup WhatsApp di Masa Covid-19 - Maila D.H. Rahiem; Veda Ria Perdana (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
The purpose of this study was to describe how online learning utilizing WhatsApp (WA) groups for early childhood (ECE) was planned, implemented, and assessed during the COVID-19 period.  This study employed a descriptive qualitative approach. The data gathering took place in an Islamic kindergarten in Tangerang, Banten, between January and April 2021. The researchers conducted interviews with three teachers and observed group B's learning activities with seventeen students. The data were examined thematically using Saldaña's two-cycle codification model. The data demonstrates that: 1) teachers planned and communicatde activity plans weekly to parents via the WA group; 2) learning occured synchronously via video calls in the WA group for 30 minutes/day/study group from Monday to Thursday using teaching methods such as demonstrations, storytelling, experiments, assignments, and questions and answers; and 3) learning also occured asynchronously via teachers sending learning videos to children to study at home with their parents. 4) Daily and weekly checklist assessments, work appraisals, and anecdotes were used to assess learning.; 5) Children took an active role in their learning, and teachers assessed their performance to be good.; and 6) parental involvement in learning is critical to learning success. Early childhood online learning via WA groups continues to be a popular alternative due to its relative ease, affordability, and practicality.Keyword: Early childhood education (ECE), distance learning, digital technology, kindergarten